Efecto del malteado y tostado de tres variedades de maíz (Zea mays) sobre las características físico-químicas y sensoriales en una bebida refrescante - Mesa Arévalo, Kassandra Abigail (2025)
The purpose of this study was to determine the effect of malting and roasting three varieties of corn (Zea mays): Guagal Mejorado INIAP-111, Mishqui Sara INIAP- 103, and Morocho Blanco, on the physical-chemical and sensory characteristics of a soft drink. The identified problem lies in the limited use of corn as a raw material in the production of natural beverages, compared to the increasing use of artificial ingredients in the industry. Through an AxBxC factorial experimental design with 18 treatments, the combined effects of variety, germination time (3, 4, and 5 days), and roasting degree (blond and dark) on parameters such as pH, acidity, °Brix, and sensory attributes (smell, flavor, color, fluidity, and acceptability) were evaluated. The research was carried out at the Agroindustrial Complex and the Laboratory of the Research Department of the State University of Bolívar. The results demonstrated significant differences between treatments, with treatment T1 (Guagal Mejorado INIAP-111, 3 days of germination, blond roasting) standing out as the most sensorially accepted, also meeting the physical, chemical, and microbiological standards established by Ecuadorian regulations. The discussion argues that the use of local corn varieties through traditional processes such as malting and roasting allows for the development of beverages with a territorial identity and high commercial potential. It is concluded that these techniques improve the nutritional and sensorial quality of the final product and that their application can foster the comprehensive use of corn, promote healthier alternatives, and contribute to local agroindustrial development. Further similar studies are recommended, including other varieties and fermentation techniques, to expand the options for food innovation.